Evaluation of torque characteristics single phase double stator BLDC permanent magnet motor : parallel and series magnetic circuit. - R. N., Firdaus; Misron, Norhisam; M., Harizan; Mariun, Norman; Aris, Ishak; Nirei, Masami; Wakiwaka, Hiroyuki (2012)
This paper describes the evaluation of torque characteristics of single phase double stator Brushless (BLDC) permanent magnet motor. The torque characteristic is evaluated based on the value of the minimum Total Harmonic Distortion (THD), the maximum fundamental torque Tf, the maximum peak torque Tp and the minimum cogging torque Tc. The investigation on the evaluation on the parallel magnetic circuit and proposed series magnetic circuit of double stator permanent magnet motor is presented. The proposed series magnetic circuit is relatively different compare to conventional series magnetic circuit since the reluctance is lower due to small amount ferromagnetic material in rotor is used while keeping the volume of permanent magnet. Finite Element Analysis (FEA) IS used to Simulate the torque waveform based on various combinations of taper parameters. MATLAB is used to determine the THD and the harmonic components of the torque waveform. The result shows the taper parameter affects the torque waveform, thus affecting the THD, Tr, Tp, and Te• Also, the motor constant square density, G is used for comparisons with other model that's is already in literature. Finally, this paper shows the selection of model based on evaluation of lowest THD, highest Tr, highest Trn, and lowest Te could play important role in designing a BLDC.